Core Surgical Training in the United Kingdom: How to Succeed in the Application Process - Mailley, Keir (The Surgery Journal, 2025)
With approximately four applicants per post, gaining a core surgical training job in the United Kingdom is a competitive endeavour. In recent years, there have been several changes to the application process and self-assessment scoring. This article aims to guide and inform applicants toward making a successful application and starting their career in surgery.
Keywords: shortlisting; application process; career progression; core surgical training